PELAKSANAAN KEGIATAN PEMBERDAYAAN MASYARAKAT DI KEPENGHULUAN RAJA BEJAMU KECAMATAN SINABOI KABUPATEN ROKAN HILIR TAHUN 2016 - Sugandi "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The administration of the village administration is a subsystem of the administration of government, so that the village has the authority to regulate and manage the interests of the community. Village Community Empowerment is an effort to develop community independence and prosperity by increasing knowledge, attitudes, skills, behavior, abilities, awareness, and utilizing resources through the establishment of policies, programs, activities, and assistance in accordance with the essence of the problems and priorities of the needs of the village community. The implementation of community empowerment activities carried out by the Raja Bejamu Kepululuan Government should be able to socialize that community participation in governance and development of Kepululuan is very important.               This study aims to describe the Implementation of Community Empowerment Activities in Raja Bejamu District Chief of Sinaboi District, Rokan Hilir District in 2016. The location of this research was conducted in Raja Bejamu District Chief of Sinaboi District. Data collection techniques are done by interview and documentation. The method used in this research is qualitative descriptive.               Empowerment emphasizes the process of giving people the ability to be empowered, encouraging or motivating individuals to have the ability or empowerment to determine their life choices. Based on the results of the study showed that the implementation of Community Empowerment Activities in the Bejamu King's Commitment in Sinaboi District, Rokan Hilir Regency in 2016 was not optimal, where the goal of implementing community empowerment for the creation of community independence had not been achieved, this was caused by the first three (3) factors due to lack of budget, the second is Quality of Human Resources, and thirdly the Lack of Participation of the Bejamu Raja Kepululuan Society. Keywords: Implementation, Society Empowerment